Sustainable Development through Universal Human Values - Ravichandran, S (Journal of Advanced Research in Humanities and Social Sciences; Vol 10 No 1 (2023): Journal of Advanced Research in Humanities and Social Sciences, 2023)
Values that are fundamental to being a person are referred to as basic human values. Truth, honesty, loyalty, love, peace are among the values that are seen as being essential human values because they highlight the core goodness of people and society. Human values are integral part of our personality. Many employers are inclined to hire those who have better human values. It is rightly to state that ‘Human being without values is none other than an animal’. But when values enter in the character of human beings then it is turned as ‘value-based education’ which not only gives moral education but also develops an overall growth of a human being. Positive values always make a good impact for the society as well as individual. Value can be evaluated in two ways. Extrinsic and intrinsic values. By example we can understandthis. Suppose, if I need 2 kg of sugar to buy, for that I have to go for shopkeeper. After paying the value of sugar, then only I can receive the material. In our life what we pay to buy material things that all are related to extrinsic values. Apart from this there are intrinsic values, Love, care, share, gratitude, reverence, trust, responsibility which we cannot buy. I can’t say I need 2kg of love or 2 meters of affection. This is absolutely impossible. Intrinsic values are so special or precious to acquire in our life. Therefore, value education implies for importance of knowledge in any kind of source. Nothing can exist without value. The axe is useful so long as it cuts, the tree so long as it bears fruit, the Cow so long as it gives milk. This rule applies to everything in the natural would for all it is interrelated. It also applicable to human beings. Practice makes a man perfect. We are useful so far as we practice over the values. Every human being with to be prosperous and happy throughout their life tenure, but how it can be attained and assessed is revealed in this article.